Low Power and High Speed D-Latch Circuit Designs Based on Carbon Nanotube FET - Talebipoor, Neda; Keshavarzian, Peiman; Irannejad, Behzad (International Journal of Engineering and Technology, 2012)
In this paper we propose low power and high speed D-latche circuits base on carbon nanotube field effect transistor. D-latches are the important state-holding elements and systems performance enhancement will be achieved by improving the flip-flop latches structure. The circuit designs are simulated by Hspice .In this paper the consumption result of the circuit parameters such as delay, power and PDP for our three different D-latch circuit design in various voltages and different temperatures.